Positronium Chemistry: Origin, Development, and Historical Roots - Helge Kragh (Substantia)
Positronium science has for more than half a century been an important research area located somewhere between physics and chemistry. Based upon the study of positrons and the electron-positron atom called positronium, the field was originally part of atomic physics but soon became embraced also by the chemists. In this article I present a first preliminary study of the origin and early history of positronium science with an emphasis on its chemical aspects. It includes a so-called prehistory going back a long time before the discovery of the positron, at a time when the ether was sometimes conceived as consisting of pairs of oppositely charged electrons. Apart from positronium, the intertwined history of muonium – where the electrons are replaced by the heavier muons – is also described. More generally, the paper discusses from a historical perspective how various kinds of exotic atoms, antiatoms and superheavy atoms included, have become parts of the chemical sciences.